Effect of Strain on Haematology and Serum Biochemical Profile of Broiler Chickens Fed Aqueous Extract of Bitter Leaf - Tella, Adetunmbi (Jordan Journal of Agricultural Sciences, 2025)
This study aimed to evaluate the effect of strain on the serum biochemical profile and hemoglobin profile of broiler chickens fed bitter leaf (Vernonia amygdalina) extract as a phytoadditive. The commercial hatchery, Mhido Farms, provided the 153-day-old broiler chicks purchased. The 153 chicks, weighing an average of 50g, were randomly assigned to one of three strain level treatments: CBR (Cobb 500), ABR (Abor acre), and RSR (Ross 300). There were three replicates of the results, each with 17 birds, and each treatment comprised 51 birds. For the experiment, a 3x3 completely randomized arrangement was employed. The chicks were raised in equidimensional boxes measuring one meter by one meter. The commercial broiler starter (22% CP and 2900 kcal/kg ME) and finisher (18% CP and 2900 kcal/kg ME) meals were provided to the birds in each treatment group in the same amounts. Additionally, they had unrestricted access to water with the same concentrations of bitter leaf extract (one liter of drinking water containing 25 milliliters of aqueous extract). The usual treatment and immunization schedule of the University Teaching and Research farm, together with ethical requirements, were followed for the birds. There were sixty days in the trial. To examine the biochemistry and haematology of the serum, a blood sample was taken. The results demonstrated that strains had a major impact on the hematological and serum biochemical profile of broiler chicks administered bitter leaf extract. WBC, RBC, and monocyte counts varied considerably (P<0.05) in AAR broiler chicks. In the serum biochemical analysis, only albumin showed a significant difference (P<0.05), with the AAR and CBR strains showing higher mean values of 18.22 and 18.17 g/L, respectively. In conclusion, bitter leaf can be added to the broiler diet as a phytoadditive, especially in strains of AAR and CBR broilers. Further study is necessary to ascertain the optimal diet formulations, including bitter leaves, for diverse breeds of broiler chickens.